Treating Frozen Shoulder with Integrative Medicine Approach by the Energy Accumulator - Kevin Ki-Wai Ho; Anthony Wai-Leung Kwok; Wai Wang Chau; Leung-Kim Hung (Journal of Orthopedics and Joint Surgery)
Background: Frozen shoulder is a painful and disabling disorder of unclear cause, affecting middle-aged people after their 5th decade. They suffer from annoying pain and limited shoulder mobility. energy accumulator provides a better way of relief through an integrative medicine concept. Objectives: This study aims to evaluate the effectiveness of localized heat therapy using the energy accumulator on acupoints combined with mobilization exercise for the treatment of frozen shoulder. Methods: Thirty-eight subjects (26 females, 12 males) of age 45–65 (mean age 55.43) were recruited. An orthopedic surgeon diagnosed frozen shoulder using Codman’s 12 criteria. An eight-session Traditional Chinese medicine (TCM) treatment applying heat and stroking massage was offered. All subjects completed the questionnaire set including Oxford Shoulder Score (OSS), Shoulder Pain & Disability Index (SPADI), and visual analog scale (VAS) for pain. Range of motion (ROM), muscle power, muscle circumference, and grip strength were measured. Results: Comparing with the controls from literature, the treatment group showed improvement in the OSS (mean change = 4.93, p < 0.01), SPADI (mean change = −18.9, p < 0.01), SF-12 physical (mean change = 2.5, p < 0.01), SF-12 mental (mean change = 2.6, p = 0.03), VAS (mean change = −0.5, p < 0.01), active ROM (mean change = 21.6, p < 0.01), and passive ROM (mean change = 23.7, p = 0.01). Conclusion: The results demonstrated an efficient and effective treatment effect of using the energy accumulator in treating frozen shoulders among middle-aged patients. This study was a good example of integrating Western medicine with the TCM for efficient and effective treatment outcomes.